2015
DOI: 10.5005/jp-journals-10024-1648
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Photo-Fenton Bleaching on Tetracycline-stained Dentin in vitro

Abstract: Aim Tetracycline-stained tooth structure is difficult to bleach using nightguard tray methods. The possible benefits of in-office light-accelerated bleaching systems based on the photo-Fenton reaction are of interest as possible adjunctive treatments. This study was a proof of concept for possible benefits of this approach, using dentine slabs from human tooth roots stained in a reproducible manner with the tetracycline antibiotic demeclocycline hydrochloride. Materials and methods Color changes overtime in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…This principle is the basis for using intense green light from green LED arrays or KTP lasers as a clinical treatment for reversing discolouration caused by the systemic use of tetracyclines during tooth formation (De Moor et al, 2015;Walsh et al, 2004). The same effect was first shown in the laboratory using aqueous solutions (Davies et al, 1979;Lin et al, 1988), and in 2015, it was demonstrated using roots with profound staining induced by demeclocycline, when treated with visible green light from a KTP laser or an array of green LEDs (Bennett & Walsh, 2015a, 2015b.…”
Section: Lightsupporting
confidence: 57%
See 2 more Smart Citations
“…This principle is the basis for using intense green light from green LED arrays or KTP lasers as a clinical treatment for reversing discolouration caused by the systemic use of tetracyclines during tooth formation (De Moor et al, 2015;Walsh et al, 2004). The same effect was first shown in the laboratory using aqueous solutions (Davies et al, 1979;Lin et al, 1988), and in 2015, it was demonstrated using roots with profound staining induced by demeclocycline, when treated with visible green light from a KTP laser or an array of green LEDs (Bennett & Walsh, 2015a, 2015b.…”
Section: Lightsupporting
confidence: 57%
“…When this happens, the luminosity of the tooth will reduce. Measuring luminosity can be used to track the darkening of tooth structure, while analysing the individual red, green and blue colour channels of digital images can reveal if there are changes in the fundamental hue of teeth because of treatment (Bennett & Walsh, 2015a).…”
Section: Interactions Of Light With Teethmentioning
confidence: 99%
See 1 more Smart Citation
“…Image analysis was undertaken using Adobe Photoshop™ CS6 Extended software, to track changes in each root over time and to calculate the colour change in red and green channels from the baseline by using a repeated measures assessment. The colour channel analysis method used was similar to that employed in previous studies [ 8 , 9 , 10 ]. The selected areas of interest were located at 250 and 500 μm from the root canal walls in a straight line.…”
Section: Methodsmentioning
confidence: 99%
“…The colour channel analysis method used was similar to that employed in previous studies. [126][127][128] An example of the analysis method is shown in Appendix A, Fig. A3.…”
Section: Tracking Colour Changes In Root Dentine Over Timementioning
confidence: 99%